Management of two teeth unerupted due to an odontoma: two years follow-up - Bezerra, Tacíria Machado; Alves, Thaís Pinto; Soares, Thaís Rodrigues; Neto, Oswaldo Costa; Costa, Maria da Encarnação P. R.; Farinhas, João A.; Ferreira, Dennis Carvalho; Gleiser, Rogério (Revista de Ciências Médicas e Biológicas, 2014)
Objective: The purpose of this case report was to describe the successful management of unerupted incisors due to an odontoma in two young girls with history of dental trauma in primary teeth. Case report: The radiographic examinations revealed odontoma-like malformations, which were surgically removed in both cases. In case 1 the crown of the permanent tooth was exposed and orthodontic traction performed and in case 2, a waiting period of at least 6 months for spontaneous eruption of permanent tooth was expected. After 8 months it was necessary the orthodontic traction because the tooth had not erupted. In both cases the correct alignment of the upper incisors was achieved, the final occlusion was satisfactory and periapical radiographs revealed no pathological signs. Conclusion: The satisfactory results confirmed the advantages of these approaches, which restored the esthetics and oral function of these two young patients.